One-to-one coupling of glacial climate variability in Greenland and Antarctica - Barbante, C.; Barnola, J.-M.; Becagli, S.; Beer, J.; Bigler, M.; Boutron, C.; Blunier, T.; Castellano, E.; Cattani, O.; Chappellaz, J.; Dahl-Jensen, D.; Debret, M.; et al. (Nature, 2022)
Precise knowledge of the phase relationship between climate changes in the two hemispheres is a key for understanding the Earth's climate dynamics. For the last glacial period, ice core studies have revealed strong coupling of the largest millennial-scale warm events in Antarctica with the longest Dansgaard-Oeschger events in Greenland through the Atlantic meridional overturning circulation. It has been unclear, however, whether the shorter Dansgaard-Oeschger events have counterparts in the shorter and less prominent Antarctic temperature variations, and whether these events are linked by the same mechanism. Here we present a glacial climate record derived from an ice core from Dronning Maud Land, Antarctica, which represents South Atlantic climate at a resolution comparable with the Greenland ice core records. After methane synchronization with an ice core from North Greenland, the oxygen isotope record from the Dronning Maud Land ice core shows a one-to-one coupling between all Antarctic warm events and Greenland Dansgaard-Oeschger events by the bipolar seesaw. The amplitude of the Antarctic warm events is found to be linearly dependent on the duration of the concurrent stadial in the North, suggesting that they all result from a similar reduction in the meridional overturning circulation. ©2006 Nature Publishing Group.